Optimising conditions and environments for digital participation in later life: A macro-meso-micro framework of partnership-building - Reuter, Arlind; Xu, Wenqian; Iwarsson, Susanne; Olsson, Tobias; Schmidt, Steven M. (Frontiers in Psychology, 2023)
The ongoing digitalisation of societies, exacerbated by the COVID-19 pandemic, has led to increased efforts to ensure the digital inclusion of older adults. Digital inclusion strategies throughout the COVID-19 pandemic predominantly focused on increasing access and basic digital literacy of Information and Communication Technologies (ICTs) for all members of society. Older adults, who are more likely to experience unintended consequences of digitalisation as a result of the COVID-19 pandemic, are amongst the target groups of digital inclusion strategies. We propose that beyond digital inclusion, there is a need to focus on digital participation and optimise opportunities for everyone to participate in communities and society in post-pandemic times. Creative digital skills are the foundation of digital participation and can lead to a variety of contributions. Digital participation offers conditions that support positive self-awareness and active contributions to a digitalised society. Taking macro-, meso-, and micro-level enablers of digital participation in later life into account, we argue for the establishment and implementation of multi-layered and multisectoral partnerships that address environmental factors (including social and physical dimensions) of digital participation and create opportunities for diverse, meaningful and fulfilling engagement with ICTs in later life. The partnership approach can be used in designing and implementing digital participation programmes and should be further evaluated against the needs and lived experiences of older individuals. Foresighted research is needed to investigate key factors of effective partnerships for optimising environments for digital participation in later life.